PEMAHAMAN MASYARAKAT TENTANG TRADISI PERMAINAN KANTOLA DI DESA BEA KECAMATAN KABAWO KABUPATEN MUNA - Nurdin Anton; Wa Ode Sifatu; Ashmarita Ashmarita (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2019)
This research aims to understand the forms of kantola tradition and people's understanding, especially those in Bea Village towards these traditional entities. Data collection is done through observation, in-depth interviews, and study of documents and literature. The results of this study indicate that the tradition of kantola games carried out periodically is an introduction to growing awareness of the community that opens opportunities for growth, and the development of traditions including the kantola tradition which is increasingly squeezed by global cultural products. Kantola has meaning that is useful in the daily lives of local people. Innovation opens opportunities for understanding the heritage of past traditions that are able to answer current issues. Preservation can be formulated as a sense of self and the strength of one's own culture, cultural awareness must be grown to give appreciation to local cultures that lead to cultural resilience.